Reduced Graphene Oxide and Poly (phenylalanine) Composite Modified Electrode for the Electrochemical Determination of Vanillin. Issue 12 (1st December 2022) - Tesfaye, Gizaw; Negash, Negussie; Tessema, Merid
Abstract : In this study, a simple, low cost and stable electrochemical sensor for vanillin is reported based on glassy carbon electrode (GCE) modified with poly (phenylalanine) and electrochemically reduced graphene oxide (ERGO) composite (poly (phenylalanine)/ERGO/GCE). The surface structure of the bare and modified electrodes was characterized by Fourier transform infrared (FTIR) and scanning electron microscopy (SEM). The electrochemical behavior of vanillin at phenylalanine)/ERGO/GCE) was also studied by CV. Poly (phenylalanine)/ERGO/GCE) exhibited high electrocatalytic activity for the electrochemical oxidation of vanillin due to the synergetic effects of poly (phenylalanine) and ERGO. From linear sweep voltammetry (LSV) study, the electrode reaction of vanillin is adsorption-controlled process. Furthermore, several electrochemical parameters such as number of electrons transferred (n = 2), number of protons transferred (H + = 2), electron transfer coefficient ( α = 0.66) and surface concentration of vanillin (Ґ = 0.32 nmol cm −2 ) were calculated. SWV was used for quantitative determination of vanillin at phenylalanine)/ERGO/GCE). Under the optimum conditions, the oxidation peak current of vanillin increased linearly with its concentration in the range 0.25–120 μ M with a low detection limit of 0.025 μ M. The developed sensor was successfully applied for the determination of vanillin in food and soft drink samples.